Terminator salvation [videorecording (DVD)] - McG (Joseph McGinty Nichol); Bale, Christian, 1974-; Worthington, Sam, 1976-; Yelchin, Anton; Bloodgood, Moon; Howard, Bryce Dallas, 1981-; Common (Musician); Alexander, Jane, 1939-; Bonham Carter, Helena, 1966- (Distributed by Warner Home Video, 2009)
The future Connor was raised to believe in is altered in part by the appearance of Marcus Wright, a stranger whose last memory is of being on death row. Connor must decide whether Marcus has been sent from the future, or rescued from the past. As Skynet prepares its final onslaught, Connor and Marcus both embark on an odyssey that takes them into the heart of Skynets operations, where they uncover the terrible secret behind the possible annihilation of mankind.